A polarization independent phase gradient metasurface for spoof plasmon polaritons coupling. (21st December 2015) - Wu, Chenjun; Cheng, Yongzhi; Wang, Wenying; He, Bo; Gong, Rongzhou
Abstract: A polarization-independent phase-gradient metasurface (PGM) is proposed, and theoretically as well as experimentally investigated, for realizing spoof surface plasmon polariton (SPP) coupling. The designed PGM is a periodic array comprising a dielectric substrate sandwiched between a metallic split cross structure and a continuous metallic film. The numerical results for the designed PGM indicate that normally incident electromagnetic waves can be efficiently coupled into spoof SPPs, since the additional wave vector generated by the designed PGM is greater than that of the incident waves. Both simulations and experiments demonstrate that the designed PGM, as a spoof SPP coupler, is insensitive to polarization, and highly efficient under normally incident X-band radiation.